2009
DOI: 10.1095/biolreprod.108.075739
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin Facilitates Exchange of Glycosyl Phosphatidylinositol-Linked SPAM1 Between Reproductive Luminal Fluids and Mouse and Human Sperm Membranes1

Abstract: Glycosyl phosphatidylinositol (GPI)-linked proteins, which are involved in post-testicular maturation of sperm and have a role in fertilization, are acquired on the sperm surface from both vesicular and membrane-free soluble fractions of epididymal luminal fluid (LF) and uterine LF. Herein, we investigate the mechanism of uptake of these proteins from the soluble fraction of LFs using sperm adhesion molecule 1 (SPAM1) as a model. Ultracentrifugation and native Western blot analysis of the soluble fraction reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…microvesicles, and exosomes, which serve as vehicles for the transfer of proteins to the sperm surface (1)(2)(3). This protein transfer during the interaction of sperm with the microenvironment in the female tract is essential for their maturation and fertilizing ability.…”
mentioning
confidence: 99%
“…microvesicles, and exosomes, which serve as vehicles for the transfer of proteins to the sperm surface (1)(2)(3). This protein transfer during the interaction of sperm with the microenvironment in the female tract is essential for their maturation and fertilizing ability.…”
mentioning
confidence: 99%
“…Immunohistochemical analysis showed that clusterin was present in spermatogenic cells besides Sertoli cells in the lumen of seminiferous tubules. As mentioned in the introduction, clusterin derived from Sertoli cells bound to the surface of testicular spermatozoa in the rete testis fluid and would be replaced by clusterin from the epididymis or seminal vesicle during sperm migration [3,8,9,32]. Therefore the clusterin observed by us in the inner membrane of normal spermatozoa may have been synthesized by the spermatogenic cells.…”
Section: Discussionmentioning
confidence: 71%
“…Most previous studies have shown that clusterin is secreted into semen by the epididymis and seminal vesicle, and mainly adheres to the surfaces of abnormal spermatozoa [3,8,9,25,32]. Only a few researchers observed clusterin in normal human spermatozoa [2,26,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein expression levels of HE2, FA-1, clusterin and PH20 were selected for verification by Western blot and RT-PCR because they play important roles in sperm maturation and fertilization process. [21][22][23][24][25][26][27][28][29] Western blot demonstrated that the content of HE2 was downregulated after reproductive tract obstruction and the downward trend was more obvious with increasing time of obstruction. Another study by Légaré et al 21 showed that vasectomy did not influence expression of HE2 in the human epididymis .…”
Section: Discussionmentioning
confidence: 99%